Forms and Characteristics of Organization of Learning Classes in General Sciences - Mirzaev Janjar; Amrullayev Behzod; Muzafarova Gulsara Sharofov Islomjon (Research Parks Publishing LLC, 2021)
In the following article the methodics of teaching the issues of energy supplies in the agriculture and irrigation. The new innovational technologies of supply of energy are discussed. The proposals are given based on the scales of national and international experience.